Evaluation of the Effectiveness of a Positive Youth Development Program for Secondary Students in Macau - Andrew L. Luk; K. M. Leong; Annah M. L. Au (The Scientific World Journal)
A well-tested comprehensive Chinese positive youth development program (Project P.A.T.H.S.) developed in Hong Kong has been modified and adapted for use in Macau. This program aims to help adolescent school children develop positively and to be better prepared for their future. The present study investigated the effectiveness of the Tier 1 Program of “P.A.T.H.S.” for Secondary 2 students of two pilot schools. Since there were “repeating” and “transferring” students joining the program, the effectiveness of the program on these particular groups of participants was also examined. The subjective outcome evaluations including participants' perceptions of the program, program instructors, benefits from the program, and overall satisfaction were positive. Although the longitudinal data from the objective outcome evaluation did not show any notable improvement, the overall effect of the program was found to be positive to the new comers in the junior secondary years. The existing evaluation findings suggest that the Secondary 2 program is especially effective to those newly joining the program. In view of the paucity of youth studies in Macau, the present study can contribute to evidence-based youth work and provide baseline data for the program to be evaluated in the Secondary 3 periods in the future.